Pathogenicity of Arcobacter cryaerophilus in two human intestinal cell lines - Antonia Bachus; Sarah Beyer; Roland Bücker; Soroush Sharbati; Thomas Alter; Greta Gölz (Gut Pathogens, 2025)
Abstract Background Arcobacter cryaerophilus is considered an emerging foodborne pathogen and is associated primarily with infectious gastrointestinal disease in humans. However, the underlying pathogenic mechanisms remain poorly understood. Therefore, the aim of the present study was to investigate the pathogenic potential of twelve A. cryaerophilus strains using various in vitro assays in two human colonic cell lines, HT-29/B6 and T84. Results All strains tested were able to adhere to and invade into both cell lines, with strain-dependent differences in their adhesion and invasion rates. In addition, two strains showed cytotoxic effects on both cell lines. The ability to disrupt the epithelial barrier function of T84 cell monolayers was shown for two strains by measurement of transepithelial electrical resistance. As structural factors correlate with the barrier dysfunction, immunofluorescence staining of the tight junction domain was performed, and revealed an altered distribution of claudin-5 in infected cells. Conclusions The results highlight the strain-dependent pathogenic mechanisms of A. cryaerophilus that may contribute to key symptoms such as diarrhoea. These findings also highlight the importance of further research into the pathogen A. cryaerophilus.